SUBLIMINAL MESSAGES OF WAR: PORTRAYAL IN “justice league flashpoint paradox” - Shakil, Hira; Amna Zulqarnain; Dr. Wajid Zulqarnain (Journal of Peace, Development and Communication, 2024)
This research examines superhero cartoon movies as a medium for narrating the perceived superiority of the West over the East, with the West depicted as the savior and the East as a threat to global peace. Using "Justice League: Flashpoint Paradox" (2013) as a case study, the study investigates the incorporation of subliminal messages related to the real-time Iraq war through hidden images and narrative elements. The research is structured using Roland Barthes’ semiotic theory employing Edward Said’s theory of Culture and Imperialism, the study analyzes visual representations in the cartoon movie to illustrate their reflection of the Iraq war and highlighting how superhero narratives reflect contemporary geopolitical tensions and reinforce Western hegemony, particularly in the context of the post-9/11 era. Furthermore, the study examines the impact of these subliminal messages on the overall narrative and characterization, revealing the perpetuation of stereotypical images of both the West and the East.